Advancing crush syndrome management: the potent role of Sodium zirconium cyclosilicate in early hyperkalemia intervention and survival enhancement in a rat model - Li, Duo; Zhang, Yan; Chen, Yuansen; Yang, Bofan; Chen, Jianwen; Shi, Jie; Guo, Xiaoqin; Liu, Yanqing; Zhang, Li; Lv, Qi; Fan, Haojun (Frontiers in Pharmacology, 2024)
Background: Crush Syndrome(CS), a severe trauma resulting from prolonged muscle compression, is commonly seen in large-scale disasters such as earthquakes. It not only causes localized tissue damage but also triggers electrolyte imbalances, particularly hyperkalemia, increasing the risk of early mortality. This study aims to assess the early intervention effects of Sodium Zirconium Cyclosilicate (SZC) on hyperkalemia in rat CS model. Methods: A rat CS model was established using a self-developed multi-channel intelligent small-animal crush injury platform. Rats in the experimental groups were treated with varying doses of SZC before compression and immediately post-decompression. The efficacy of SZC was evaluated by continuous monitoring of blood potassium levels and survival rates. Serum creatinine (Cre) and blood urea nitrogen (BUN) levels were analyzed, and renal damage was assessed through histopathological examination. Results: SZC treatment significantly reduced blood potassium levels and improved survival rates in rats.Compared to the placebo group, the SZC-treated rats showed a significant decrease in blood potassium levels at 6 and 12 h post-decompression, maintaining lower levels at 24 h. Biochemical analysis indicated no significant impact of SZC on renal function, with no notable differences in Cre and BUN levels between groups. Histopathological findings revealed similar levels of renal damage in both groups. Conclusion: SZC demonstrates significant early intervention effects on hyperkalemia in a rat model of crush injury, effectively improving survival rates without adverse effects on renal function. These results provide a new strategic direction for the clinical treatment of Crush Syndrome and lay the foundation for future clinical applications.